2013
DOI: 10.1016/j.jval.2013.08.651
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal Insufficiency: Burden of Disease and Cost of Illness

Abstract: ments. In addition, diabetic patients with low education level cost 2.341€ cost more on average in comparison to better educated patients. ConClusions: T2DM is an expensive to treat disease and in the era of limited resources and escalating costs it is critical to implement sound public health policies in order to achieve patient's good glycemic control and consequently less burden to health care budgets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The UK cost of illness study suggested that inpatient admissions are a major cost driver of AI [ 5 ]. In a recent analysis, using the same cohorts as the current study, we found hospital inpatient admissions to be significantly higher in AI patients vs controls: for one admission in the matched control group, there were 4.64 admissions in the PAI cohort P < 0.0001.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The UK cost of illness study suggested that inpatient admissions are a major cost driver of AI [ 5 ]. In a recent analysis, using the same cohorts as the current study, we found hospital inpatient admissions to be significantly higher in AI patients vs controls: for one admission in the matched control group, there were 4.64 admissions in the PAI cohort P < 0.0001.…”
Section: Discussionmentioning
confidence: 99%
“…The literature on cost of treatment of AI is very limited. A recent study involving about 20,000 patients in the United Kingdom estimated the cost per patient of £1922 (USD $3,411) giving a total annual cost for the AI patient population of the UK of £39.7 million (USD $70.5 million) [ 5 ]. There are several cost drivers of AI that include but are not limited to diagnosis, less efficacious treatment strategies, comorbidities associated with the underlying disease, and possible side effects induced by the glucocorticoid replacement.…”
mentioning
confidence: 99%
“…AI poses a significant health burden on patients, their families, and the healthcare system. A UK study in 2013 estimated an annual cost of illness associated with AI at £39.7 million for approximately 20,000 patients ( 16 ). Health care cost for patients with AI is four times higher than for the general population ( 17 ).…”
Section: Introduction: Self-management For Patients With Adrenal Insu...mentioning
confidence: 99%